How Multimedia Learning Enhances Students' Mathematical Creativity in Science Education: A Meta-Analysis Study - Yusuf Al-Amin; Sugiman Sugiman (Jurnal Penelitian Pendidikan IPA, 2024)
Many studies have examined the impact of multimedia learning on students' mathematical creativity, but the results are mixed. As multimedia learning has been researched for decades in various subjects and schools, this meta-analysis study aims to synthesize the latest findings on the impact of multimedia learning, particularly on students' mathematical creativity in science learning. Data were obtained from relevant primary research published in national and international journals or proceedings during 2016-2023. This research design uses a meta-analysis approach by analyzing 33 effect size studies that meet the inclusion criteria using systematic review and meta-analysis. The role of science in this context is to ensure that an understanding of students' mathematical creativity is accompanied by a deep understanding of the underlying scientific principles. JASP software was used to measure the Hedges g formula to determine the effect size. The results showed that multimedia learning influences students' mathematical creativity (gRE = 0.768; 95% CI [0.654; 0.882]; p < 0.001) when compared to traditional learning. The results of this study provide important information for further meta-analysis studies and the application of multimedia learning to improve students' mathematical creativity in science learning.